2011
DOI: 10.1002/zoo.20329
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of a zoo‐housed infant orangutan after the death of its mother

Abstract: The behavior of an infant female orangutan at Dublin Zoo before and after the death of her mother was recorded using scan sampling and compared. Social interactions and associations of the infant with the other individuals in the group were also compared before and after the death of her mother. Increases in climbing and object manipulation were observed, and a decrease in resting occurred. The infant orangutan significantly increased the amount of time she spent in close contact with another related adult fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Behaviors were classified, based on behavioral similarity or apparent behavioral ends, into four types: visual, aggressive, hiding, and affiliative (see Table II for full descriptions of HDBs). Additionally, affiliative behaviors, were designated as close (<3 m) or distant (>3 m), consistent with proximity definitions for studies of zoo orangutans and gorillas [Edwards & Snowdon, 1980;Less et al, 2010;Nakamichi & Kato, 2001;Poole, 1987;Stoinski et al, 2003Stoinski et al, , 2004Whilde & Marples, 2011;Zucker & Thibaut, 1995].…”
Section: Observationsmentioning
confidence: 99%
“…Behaviors were classified, based on behavioral similarity or apparent behavioral ends, into four types: visual, aggressive, hiding, and affiliative (see Table II for full descriptions of HDBs). Additionally, affiliative behaviors, were designated as close (<3 m) or distant (>3 m), consistent with proximity definitions for studies of zoo orangutans and gorillas [Edwards & Snowdon, 1980;Less et al, 2010;Nakamichi & Kato, 2001;Poole, 1987;Stoinski et al, 2003Stoinski et al, , 2004Whilde & Marples, 2011;Zucker & Thibaut, 1995].…”
Section: Observationsmentioning
confidence: 99%
“…Goodall () also recounts the case of the juvenile Pax who became agitated and screamed following his mother's (Passion) death, constantly pulling her hand and carrying out a vigil with his two elder siblings, moving away before nightfall. Successful adoptions have a positive effect, as seen in a captive orangutan that spent more time in physical contact with her aunt after her mother died and showed no significant self‐directed behaviours (Whilde & Marples, ).…”
Section: Primate Thanatology: Contemporary Reportsmentioning
confidence: 99%
“…The same thing was seen in feeding activity, which would increase with age (7-22% at age 1 year to 30% at age 3 years) (Mendonca et al 2016). Another result showed that one orangutans infant in Dublin Zoo spent 43.4% for resting (when its mother alive) but fell significantly to 28.9% without its mother (Whilde and Marples 2010). Meanwhile, in reintroduction orangutans, the most significant activity was feeding (53.5%-62.05%) and resting (19.52%-64.67%) (Basalamah et al 2018;Bani et al 2018).…”
Section: Discussionmentioning
confidence: 71%